2020
DOI: 10.20944/preprints202004.0097.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Convalescent Plasma Therapy for Covid-19: State of the Art

Abstract: Convalescent blood product therapy has been introduced since early 1900s to treat emerging infectious disease based on the evidence that polyclonal neutralizing antibodies can reduce duration of viremia. Recent large outbreaks of viral diseases for whom effective antivirals or vaccines are still lacking has revamped the interest in convalescent plasma as life-saving treatments. This review summarizes historical settings of application, and surveys current technologies for collection, manufacturing, pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
46
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 48 publications
0
46
0
1
Order By: Relevance
“…( Wang et al, 2020 ) ( Beigel et al, 2020 ) ( Goldman et al, 2020 ) ( Spinner et al, 2020 ) In our second patient, convalescent plasma appeared to be an effective adjunctive treatment in helping to clear the virus quickly, noted by the significant weekly increase in Ct values following administration of convalescent plasma. ( Focosi et al, 2020 ) ( Liu et al, 2020 ) ( Joyner et al, 2020 ) Convalescent plasma and monoclonal antibodies may be important treatments for those patients who are incapable of producing a humoral or T cell-mediated immune response, especially if prolonged high levels of viral shedding continue to pose a transmission risk to others.…”
Section: Discussionmentioning
confidence: 99%
“…( Wang et al, 2020 ) ( Beigel et al, 2020 ) ( Goldman et al, 2020 ) ( Spinner et al, 2020 ) In our second patient, convalescent plasma appeared to be an effective adjunctive treatment in helping to clear the virus quickly, noted by the significant weekly increase in Ct values following administration of convalescent plasma. ( Focosi et al, 2020 ) ( Liu et al, 2020 ) ( Joyner et al, 2020 ) Convalescent plasma and monoclonal antibodies may be important treatments for those patients who are incapable of producing a humoral or T cell-mediated immune response, especially if prolonged high levels of viral shedding continue to pose a transmission risk to others.…”
Section: Discussionmentioning
confidence: 99%
“…Given the fact that convalescent plasma therapy was used successfully in the 2002–2003 SARS pandemic 215 as well as the 2011 MERS outbreak, 216 plasma therapy was among the first therapies used in the COVID‐19 pandemic 21,217,218 . In the United States, the Food and Drug Administration has approved 12 trials in the National COVID‐19 Convalescent Plasma Project, which is led by the Mayo Clinic.…”
Section: Therapy Of Sars‐cov‐2 Infections Based On the Pathogenesis Omentioning
confidence: 99%
“…In SARS, 5 mL/kg of plasma at a titer ≥1:160 was utilized ( Cheng et al, 2005 ). Such titer needs to be specified through the viral neutralization assay (VNT), thus obviating any bias from the use of diverse surrogate tests having poor correlation with the VNT ( Focosi et al, 2020a , Focosi et al, 2020b , Focosi et al, 2020c ). Additionally, given the fast-declining kinetics of nAb titers, the VNT should be assessed on each donated unit in the case of repeated donations, rather than assuming the same value across multiple donations.…”
mentioning
confidence: 99%
“…The data available suggest that late stage disease (ICU admission/ventilator support) is unlikely to respond to CCP therapy ( Agarwal et al, 2020 ), with several authors suggesting an optimal window as short as 44 h post-hospitalization for transfusing CCP ( Salazar et al, 2020a , Salazar et al, 2020b ). It is a well-known phenomenon that nAb titer correlates with the severity of symptoms in COVID-19 patients ( Focosi et al, 2020a , Focosi et al, 2020b , Focosi et al, 2020c ) and preliminary reports suggested that CCP was only effective in early stage disease ( Focosi et al, 2020a , Focosi et al, 2020b , Focosi et al, 2020c ), thus trials targeting late treatment in severe patients are unlikely to produce useful insights. Limiting RCTs to early stage disease, despite the limitations imposed on the modality, should allow a higher probability of success.…”
mentioning
confidence: 99%
See 1 more Smart Citation